(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: From this one how many billions of years before land hard rock and from the rocks consists of was. To him water , wind , heat and Cold the air temperature effect reached decayed and to the soil turned .Harvest was on the ground plants , animals appear was .